2022
DOI: 10.3389/fenvs.2022.989267
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in soil induce a new microbial habitat, with consequences for bulk soil microbiomes

Abstract: Microplastic (MP) pollution poses a threat to agricultural soils and may induce a significant loss of the soil quality and services provided by these ecosystems. Studies in marine environments suggest that this impact is mediated by shifts in the microbiome. However, studies on the mode of action of MP materials on the soil microbiome are rare, particularly when comparing the effects of different MP materials. In this study, we characterized the microbiota colonizing two different MP materials, granules made o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 76 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…Some recent studies revealed an effect of MPs on the abundance and the diversity of soil microbial communities. MPs made of PolyPropylene and expanded PolyStyrene were found to create a distinct habitat for bacteria, and induce the recruitment of specific groups, such as Actinobacteria, known as plastic-degraders (Kublik et al 2022 ). As a result, clear differences were measured in the community composition of MP-spiked soils compared to the bulk soil.…”
Section: Weed Management Tillage and Mulchingmentioning
confidence: 99%
“…Some recent studies revealed an effect of MPs on the abundance and the diversity of soil microbial communities. MPs made of PolyPropylene and expanded PolyStyrene were found to create a distinct habitat for bacteria, and induce the recruitment of specific groups, such as Actinobacteria, known as plastic-degraders (Kublik et al 2022 ). As a result, clear differences were measured in the community composition of MP-spiked soils compared to the bulk soil.…”
Section: Weed Management Tillage and Mulchingmentioning
confidence: 99%
“…For example, pesticides were shown to adsorb stronger on polyethylene (PE) mulch film (584–2284 µg pesticide g −1 plastic) than on soil particles (13–32 µg pesticide g −1 soil) (Ramos et al., 2015). The alteration in MPs physicochemical properties due to the aging process (e.g., UV irradiation, thermal and biological degradation) can trigger different chemical effects of aged MPs in contrast to fresh plastics in the environment (Kublik et al., 2022). MPs can be distributed in the soil environment for a long time and exposed to UV irradiation, oxidation reactions, thermal degradation, and biodegradation.…”
Section: Abiotic Impacts Of Mps On Soil Propertiesmentioning
confidence: 99%
“…The results of functional prediction confirmed that the abundance of taxa with the functional potential of fermentation and chemoheterotrophy was significantly higher in the phycosphere than in the control seawater (Figure 7B). The major biomarker genera to differentiate bacteria in the phycosphere from those in control seawater including the organic matter decomposers that specialize in degrading complex biological macromolecules and algal debris such as Lutibacter, Maribacter, Spirochaeta, Glaciecola, and TM7a (Califano et al, 2020;Qu et al, 2021;Kublik et al, 2022) (Figure S6A). The results above suggest that biodegradability and organic nutrition preference may be the main reasons for the enrichment of related taxa in the phycosphere.…”
Section: Organic Nutrition Preference and Environmental Pressure Adap...mentioning
confidence: 99%
“…In our study, the opportunistic populations, such as members of APV groups were more abundant in the phycosphere during the early phases (Figure S6B, C), which may be due to the higher bioavailability of algal-derived metabolites released by healthy algae. Members of the TM7 cluster and CFB group (Cytophaga-Flavobacter-Bacteroides) with ability to efficiently degrade complex carbon sources (Qu et al, 2020;Kublik et al, 2022) were significantly highly abundant in the phycosphere during the late phases (Figures S6B, C), which may be related to the increase in the release of macromolecular algal-derived metabolites (i.e., polysaccharides and proteins) due to the aging and cell lysis of U. prolifera.…”
Section: Changes In the Composition And Concentration Of Organic Matt...mentioning
confidence: 99%